Delayed type of allergic skin reaction to Candida albicans in eosinophilic rhinosinusitis cases - Wakayama, Nozomu; Matsune, Shoji; Okubo, Kimihiro (Auris, nasus, larynx, 2018)
Eosinophilic chronic rhinosinusitis (ECRS) is frequently complicated by asthma, and recognized as refractory and persistent rhinosinusitis. However, the detailed pathophysiology of ECRS has not been elucidated yet. In this study, we investigated the association between recurrent ECRS and intradermal testing to multi-antigens including Candida albicans. The subjects were 49 cases of bilateral chronic rhinosinusitis including 24 ECRS cases. They underwent endoscopic sinus surgery and submitted to pathological examination. Prior to surgery, peripheral blood eosinophil count, total and antigen-specific IgE levels (11 categories), and intradermal tests (5 categories) were carried out in all patients. These patients were followed-up for longer than 3 months. We compared the results of preoperative and postoperative clinical examination data between ECRS and non-ECRS (NECRS) cases. Positive reaction of the delayed type of intradermal testing to C. albicans was significantly more often observed in ECRS than NECRS cases. (P<0.01) Additionally, these positive reaction cases exhibited significantly higher recurrence of nasal polyps and symptoms of ECRS (P<0.05). These results suggest the involvement of (Coombs) type IV allergic reaction to C. albicans in the pathophysiology of ECRS.